Insights on virulence from the complete genome of Staphylococcus capitis - Cameron, David; Jiang, Jhih-Hang; Hassan, Karl; Elbourne, Liam; Tuck, Kellie; Paulsen, Ian; Peleg, Anton (Frontiers in Microbiology, 2015)
Staphylococcus capitis is an opportunistic pathogen of the coagulase negative staphylococci (CoNS). Functional genomic studies of S. capitis have thus far been limited by a lack of available complete genome sequences. Here, we determined the closed S. capitis genome and methylome using Single Molecule Real Time (SMRT) sequencing. The strain, AYP1020, harbors a single circular chromosome of 2.44 Mb encoding 2304 predicted proteins, which is the smallest of all complete staphylococcal genomes sequenced to date. AYP1020 harbors two large mobile genetic elements; a plasmid designated pAYP1020 (59.6 Kb) and a prophage, ΦAYP1020 (48.5 Kb). Methylome analysis identified significant adenine methylation across the genome involving two distinct methylation motifs (1,972 putative 6-methyladenine (m6A) residues identified). Putative adenine methyltransferases were also identified. Comparative analysis of AYP1020 and the closely related CoNS, S. epidermidis RP62a, revealed a host of virulence factors that likely contribute to S. capitis pathogenicity, most notably genes important for biofilm formation and a suite of phenol soluble modulins (PSMs); the expression/production of these factors were corroborated by functional assays. The complete S. capitis genome will aid future studies on the evolution and pathogenesis of the coagulase negative staphylococci.